2022
DOI: 10.1002/star.202100268
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant and Antibacterial Activities of the Pyridine‐4‐Aldehyde Schiff Bases Grafted Chloracetyl Chitosan Oligosaccharide Derivatives

Abstract: As a reactive intermediate, chloracetyl chitosan oligosaccharide (CACS) can be nucleophilic substituted by some bioactive groups to give novel derivatives of chitosan oligosaccharide (COS). The Schiff bases of pyridine‐4‐aldehyde are grafted onto CACS to give four COS derivatives in this paper. Specific structural characterization is implemented by fourier‐transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR). The degree of substitution (DS) of COS derivatives is quantitatively calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Thiazole substituted has a lot of interest due to its vast range of biological activity, such as anti-cancer [17][18][19], anti-bacterial [20], anti-inflammatory [21], anti-oxidant [22], and anti-epileptic [23]. On the other hand, the pyridine moiety also shows wide biological activities as anti-bacterial, anti-oxidant [24], and anticancer [25,26]. Pyridine represents the skeletal backbone of many therapeutic agents [27] (Fig.…”
Section: Open Accessmentioning
confidence: 99%
“…Thiazole substituted has a lot of interest due to its vast range of biological activity, such as anti-cancer [17][18][19], anti-bacterial [20], anti-inflammatory [21], anti-oxidant [22], and anti-epileptic [23]. On the other hand, the pyridine moiety also shows wide biological activities as anti-bacterial, anti-oxidant [24], and anticancer [25,26]. Pyridine represents the skeletal backbone of many therapeutic agents [27] (Fig.…”
Section: Open Accessmentioning
confidence: 99%
“…In a recent study, many chitosan derivatives containing Schiff bases were synthesized. In this study, the structural characterization of chloracetyl chitosan oligosaccharide derivatives grafted with pyridine-4-aldehyde Schiff bases was performed, and their antioxidant activities against DPPH‧ radical and O 2 ‧– were determined [ 68 ]. Similarly, it was indicated that some chiral selenite ligands and their palladium complexes have antioxidant activity, which increased with concentration [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tan et al synthesized CS-bearing pyridinium salt along with quaternary ammonium salt (DS: 35-97%) (3p) through a treat-ment between CS and narcotic acid, followed by a reaction with bromopropyl trialkyl ammonium bromides [115]. In another study, Guo et al also introduced CS derivatives that contain pyridine-bearing Schiff bases (3q, DS: 22.7-50%) [116] and heterocyclic scaffolds along with thiourea (3r, 3s; DS: 21-91%, 18-88%) [98,117]. In contrast with these conventional approaches, the Zincke reaction has been explored for the direct transformation of primary amines into N-aryl pyridinium salt [118].…”
Section: Quaternary Ammonium Chitosan Derivativesmentioning
confidence: 99%